Who Avoids and Who Escapes from Poverty during the Transition? : Evidence from Polish Panel Data, 1993 96 - Okrasa, Włodzimierz (The World Bank, 1999)
November 1999 - There is a tendency toward chronic, long-term poverty in Poland. Most at risk: larger households, farm households, and households dependent on social welfare. Least at risk: households of employees or the self-employed, educated households, households headed by pensioners, households that are part of kinship networks, and households with liquid assets, durables, or access to financial resources. Among those who missed out on the benefits of the first phase of economic prosperity, children are overrepresented. Okrasa uses four-year panel data from Poland's Household Budget Survey to explore the distinction between transitory and long-term poverty, a crucial distinction in designing and evaluating poverty reduction strategies. Okrasa analyzes household welfare trajectories during the period 1993-96, to identify the long-term poor and to determine how relevant household asset endowments are as determinants of household poverty and vulnerability over time. He concludes that the chronically poor constitute a distinct and separate segment of the population, with low turnover. Among specific observations about factors that affect Poland's long-term poverty: · Variables in human capital significantly affected the pattern of repeated poverty and vulnerability. Larger households tended to experience poverty and vulnerability, mostly because they contained more children or other dependents. Households with elderly members and those headed by older people, by women rather than men, and by educated people of either gender were least likely to be poor. Poverty was unaffected by the presence of a disabled person in the household. · Households with liquid assets or durables, or with access to financial resources, were less likely to be poor and vulnerable.